Implementation of Reflective Teaching in Daily Lesson Planning for Secondary School Teachers in Batu Pahat District - Rahmat, Hilmi Nasri; Hamid, Hashima (Research and Innovation in Technical and Vocational Education and Training, 2023)
The implementation of reflective teaching is an important element in the daily lesson plan for teachers to improve the quality of teaching and improve teaching professionalism. The implementation of this reflective teaching will help teachers to implement the reflective process based on elements of heart whispering, new awareness, analysis, and suggestions for improvement to the planned teaching plan. Therefore, this study aims to identify the elements in the implementation of reflective teaching and the daily lesson plan, examine the dominant elements between the implementation of reflective teaching and the daily lesson plan, and examine the relationship between the implementation of reflective teaching and the daily lesson plan. The sampling of this study involved a total of 51 teachers from 3 secondary schools in Batu Pahat District. The research design is a survey design using a quantitative approach. This study uses descriptive and correlational data. A questionnaire was used in this study as a data collection method. The findings of the study to examine the elements in the implementation of reflective teaching obtained elements of heart whispers, elements of new awareness, elements of analysis, and elements of improvement suggestions while examining the elements of the daily lesson plan obtained elements of general information, teaching objective elements, teaching elements and assessment elements. Next, the findings of the study found that the element of new awareness and the element of general information obtained the dominant elements. Finally, there is a significant relationship between the implementation of reflective teaching and the daily lesson plan among the teachers at the secondary schools in Batu Pahat district. Therefore, the Ministry of Education can practice reflective teaching in daily lesson plans and conduct research by identifying and further analyzing the elements found in reflective teaching so that the scope of reflective teaching is wider and more varied.